Auditory function in presbycusis: peripheral vs. central changes - Mazelová, Jana; Popelar, Jiri; Syka, Josef (Experimental gerontology, 2003)
The hearing abilities of a group of 30 elderly (67-93 yr of age) subjects were compared with those of a group of 30 young (19-27 yr of age) normal hearing volunteers with the aim of characterizing the changes in the peripheral and central parts of the auditory system. In elderly subjects the pure-tone thresholds were typically represented by a gradually sloping curve with a significantly greater decline in men than in women at frequencies of 3 and 4 kHz. In spite of pure tone threshold elevation in the elderly, the difference limen for intensity at 1 and 3 kHz were not significantly smaller than in the young subjects. The incidence and levels of spontaneous, transient and distortion product otoacoustic emissions were low, which would suggest the involvement of outer hair cell pathology. Also, contralateral suppression was less marked in elderly than in young subjects. Speech audiometry in the elderly revealed serious difficulties in understanding speech. Deteriorated temporal resolution, as demonstrated by increased gap detection thresholds, correlated significantly with increased speech recognition thresholds. The results support the view that presbycusis represents a combination of deteriorated function of the auditory periphery with deteriorated function of the central auditory system.
Keywords: Humans; otoakustické emise spontánní; Audiometry, Pure-Tone; Female; Aged; dospělí; audiometrie čistými tóny; senioři; lidé; Otoacoustic Emissions, Spontaneous; Adult; ženské pohlaví; Male; presbyakuze; testy sluchového rozlišování; Aged, 80 and over; Speech Discrimination Tests; senioři nad 80 let; mužské pohlaví; Presbycusis